Asian sacred natural sites: philosophy and practice in protected areas and conservation - Verschuuren, Bas; Furuta, Naoya (Routledge, Taylor & Francis Group, Earthscan from Routledge, 2016)
Introduction : re-awakening the power of place : ancient philosophy and practice with current relevance for protected areas and conservation in Asia / Bas Verschuuren -- The Asian philosophy of protected areas / Amran Hamzah -- Sacred mountains in Asia : themes and implications for protected areas / Edwin Bernbaum -- Can world heritage status help protect sacred sites in Asia? / Alison Ormsby, Wendy Jackson and Shonil Bhagwat -- The sacred geography of Kyrgyzstan : an unrecognized network of community-conserved areas and traditional practices / Aitpaeva Gulnara -- Sacred mandala : protecting Bhutan's sacred natural sites / Liza Zogib, Khenpo Phuntshok Tashi, Tshewang Gyalpo, Sangay Dendhup, Riamsara Kuyakanon, Kelzang Wangchuk, Lopen Namgay Tenzin and Ngawang Gyeltshen -- Indian sacred natural sites : ancient traditions of reverence and conservation explained from a Hindu perspective / Rana P.B. Singh and Pravin S. Rana -- Interface between sacred natural sites and formal protected areas for biodiversity conservation in Nepal / Jailab Kumar Rai and Sudeep Jana -- Customary laws governing the sacred natural sites of the Xe Champhone Ramsar site in Lao PDR : implications for site management / Raphaël Glémet, Patricia Moore, Ketsana Phommachanh and Minavanh Pholsena -- Sacred natural sites in a legal context : a focus on the legal interpretation of the sacred/cultural heritage of the Dongaria Kondhs in India / Radhika Borde -- Forum Pekaseh in the management of Subak landscape of Catur Angga Batukaru, Unesco world heritage sites in Bali / Antoinette Royo, Wiwik Dharmiasih and Yunus Arbi -- The pa'oh's governance system and Kakku : implications for heritage conservation from Burma/Myanmar / Jonathan Liljeblad -- Kailash sacred landscape : bridging cultural heritage, conservation and development through a transboundary landscape approach / Abhimanyu Pandey, Rajan Kotru and Nawraj Pradhan -- Mount Fuji's history as a spiritual realm and means for its preservation / Toshihiko Ono, Tetsuro Hongo and Kiyotatsu Yamamoto -- Animism and traditional knowledge disappear in Virachey National Park, Cambodia / Gregory McCann and Yi-Chung Hsu -- Holy hills : sanctuaries of biodiversity in Xishuangbanna, south west China / Lily Zeng and Gaëtan Reuse -- Lakes of the gods : sacred high altitude lakes of Uttarakhand, India / Jatinder Kaur and Khima Nand Balodi -- Issyk Kul Lake, the planet's third eye : sacred sites in Issyk Kul Biosphere Reserve / Aibek Samakov and Fikret Berkes -- Tsum sacred conservation area in Gorkha, Nepal / Jailab Rai and Nima Lama -- Past and present biocultural significance of sea turtles for local communities on the Arabian Peninsula in western Asia / Vanda Mendonca, Boutros Abi-Aoun and Mohamed El Baradey -- Lua people : traditions, beliefs and sacred natural sites in northern Thailand / Narong Pongpandecha and Ken Taylor -- Creating new discursive terrain for the custodians of the Tibetan spiritscape in north west Yunnan / John Studley and Awang Jikmed -- Where culture and nature meet : recreating spiritual and religious practices for site management and governance in Takht-e Soleyman Lake, Iran / Minoo Hassani Esfehani -- The role of Tuvan people's scared natural sites in nature conservation in China / Yuxin Hou -- Conclusions : the way forward for sacred natural sites and conservation in Asia / Bas Verschuuren
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Östliche Philosophie; Naturschutz; Heiligtum; Asien